Lipocalin 2 – mutation screen and serum levels in patients with anorexia nervosa or obesity and in lean individuals - Zheng, Yiran; Rajcsanyi, Luisa Sophie; Kowalczyk, Manuela; Giuranna, Johanna; Herpertz-Dahlmann, Beate; Seitz, Jochen; de Zwaan, Martina; Herzog, Wolfgang; Ehrlich, Stefan; Zipfel, Stephan; Giel, Katrin; Egberts, Karin; et al. (Frontiers in Endocrinology, 2023)
Context The bone-derived adipokine lipocalin-2 is relevant for body weight regulation by stimulating the leptin-melanocortin pathway. Objective We aimed to (i) detect variants in the lipocalin-2 gene (LCN2) which are relevant for body weight regulation and/or anorexia nervosa (AN); (ii) describe and characterize the impact of LCN2 and MC4R variants on circulating lipocalin-2 level. Methods Sanger sequencing of the coding region of LCN2 in 284 children and adolescents with severe obesity or 287 patients with anorexia nervosa. In-silico analyses to evaluate functional implications of detected LCN2 variants. TaqMan assays for rare non-synonymous variants (NSVs) in additional independent study groups. Serum levels of lipocalin-2 were measured by ELISA in 35 females with NSVs in either LCN2 or MC4R, and 33 matched controls without NSVs in the two genes. Results Fourteen LCN2-variants (five NSVs) were detected. LCN2-p.Leu6Pro and p.Gly9Val located in the highly conserved signal peptide region may induce functional consequences. The secondary structure change of lipocalin-2 due to LCN2-p.Val89Ile may decrease solubility and results in a low lipocalin-2 level in a heterozygotes carrier (female recovered from AN). Lean individuals had lower lipocalin-2 levels compared to patients with obesity (p = 0.033). Conclusion Lipocalin-2 levels are positively associated with body mass index (BMI). Single LCN2-variants might have a profound effect on lipocalin-2 levels.